Estimating footprints of model operations - Jeanneret, Cédric; Glinz, Martin; Baudry, Benoit (2011 33rd International Conference on Software Engineering (ICSE), 2011)
When performed on a model, a set of operations (e.g., queries or model transformations) rarely uses all the information present in the model. Unintended underuse of a model can indicate various problems: the model may contain more detail than necessary or the operations may be immature or erroneous. Analyzing the footprints of the operations - i.e., the part of a model actually used by an operation - is a simple technique to diagnose and analyze such problems. However, precisely calculating the footprint of an operation is expensive, because it requires analyzing the operation's execution trace. In this paper, we present an automated technique to estimate the footprint of an operation without executing it. We evaluate our approach by applying it to 75 models and five operations. Our technique provides software engineers with an efficient, yet precise, evaluation of the usage of their models.